Wild Things : Nature, Culture, and Tourism in Ontario, 1790-1914. (University of Toronto Press, 1995)
The first book to explore the cultural foundations of tourism in Ontario, Wild Things also makes a major contribution to the literature on the wilderness ideal in North America.